G Protein-Coupled Receptor Kinase 4 Is a Novel Prognostic Factor in Hepatocellular Carcinoma. (20th June 2022) - Luo, Yunxiu; Wang, Ziyi; Xiao, Shengjun; Li, Ruirui; Jiang, Xiaoshan
Abstract : Purpose . We previously reported that G protein-coupled receptor kinase (GRK) 4 halts cell cycle progression and induces cellular senescence in HEK293 cells. The present study was aimed at assessing the prognostic value of GRK4 in hepatocellular carcinoma (HCC). Methods . GRK4 expression was detected by immunohistochemistry in paired tumoral and peritumoral tissues of 325 HCC patients. One hundred and twenty-six patients from Western China were utilized as a training cohort to develop a nomogram, while 86 patients from Eastern China were used as a validation cohort. The proliferation and migration of lentiviral-GRK4 expressing HepG2 cells were determined by MTT and wound healing assays. Results . GRK4 was differentially expressed in HCC tissues. Tumoral GRK4 intensity, tumor type, and T stage were independent prognostic factors and used to form a nomogram for predicting overall survival (OS), which obtained a good concordance index of 0.82 and 0.77 in training and validation cohort, respectively. The positive and negative prediction values with nomogram were, respectively, 83% and 75% in training cohort and 100% and 52% in validation cohort. Patients with nomogram scores > 32 and 78 showed high risk for OS. Proliferation and motility capabilities were significantly restrained in GRK4-overexpressing HCC cells. Discussion . Low GRK4 expression in HCC tumor tissues indicates poor clinical outcomes. A prognostic nomogram including tumoral GRK4 expression would improve the predictive accuracy of OS in HCC patients. We also demonstrated that GRK4 overexpression inhibits proliferation and migration of HCC cells. The molecular mechanism underlying is worth further study.